Precision toxicology shows that troxerutin alleviates ochratoxin A–induced renal lipotoxicity. Issue 2 (24th September 2018) - Yang, Xuan; Xu, Wentao; Huang, Kunlun; Zhang, Boyang; Wang, Haomiao; Zhang, Xueqin; Gong, Lijing; Luo, Yunbo; He, Xiaoyun
ABSTRACT: Lipotoxicity is the most common cause of severe kidney disease, with few treatment options available today. Precision toxicology can improve detection of subtle intracellular changes in response to exogenous substrates; thus, it facilitates in‐depth research on bioactive molecules that may interfere with the onset of certain diseases. In the current study, troxerutin significantly relieved nephrotoxicity, increased endurance, and improved systemic energy metabolism and renal inflammation in OTA‐induced nephrotic mice. Lipidomics showed that troxerutin effectively reduced the levels of triglycerides, phosphatidylcholines, and phosphatidylethanolamines in nephropathy. The mechanism was partly attributable to troxerutin in alleviating the aberrantly up‐regulated expression of sphingomyelinase, the cystic fibrosis transmembrane conductance regulator, and chloride channel 2. Renal tubular epithelial cells, the main site of toxin‐induced accumulation of lipids in the kidney, were subjected to transcriptomic profiling, which uncovered several metabolic factors relevant to aberrant lipid and lipoprotein metabolism. Our work provides new insights into the molecular features of toxin‐induced lipotoxicity in renal tubular epithelial cells in vivo and demonstrates the function of troxerutin in alleviating OTA‐induced nephrosis and associated systemic energy metabolism disorders.—Yang, X., Xu, W., Huang, K., Zhang, B., Wang, H., Zhang, X., Gong, L., Luo, Y., He, X. Precision toxicology shows that troxerutin alleviates ochratoxin A‐induced renal lipotoxicity. FASEB J. 33, 2212–2227 (2019). www.fasebj.org